Penerapan Persyaratan Umum Instalasi Listrik Dan Standarisasi Kelistrikan Di Kelurahan Maharani Kecamatan Rumbai - Tanjung, Abrar; Hamzah, Hamzah; Setiawan, David (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2021)
Electrical energy is a basic necessity for the community, because without electricity, people's activities as consumers will be disrupted. A good electrical installation that meets the Indonesian National Standard (SNI) and the National Electricity Company Standard (SPLN) as well as the General Requirements for Electrical Installation 2011 will be able to minimize problems in the installation of electrical installations. Based on the results of counseling, it was found that activity partners obtained an increase in knowledge about basic knowledge of electrical installations after extension by 75%, Partners were able to find out about PUIL 2011 after counseling by 90%, activity partners received an increase in electricity standardization after extension by 90%, activity partners knew and understand in the installation of electrical installations in accordance with PUIL after counseling by 90% and Partners know that the installed electrical equipment is in accordance with standardization after counseling by 90%.